2010
DOI: 10.1007/s10661-010-1460-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organochlorine pesticide residues in animal feed

Abstract: Animal products like milk and meat are often found to be contaminated with residues of persistent pesticides and other toxic substances. The major source of entry of these compounds to animal body is the contaminated feed and fodder. So, unless the residues are managed at this stage, it is very difficult to prevent contamination in milk and meat. Therefore, the status of residue level of most persistent organochlorinated pesticides (OCP) in feed and fodder should be monitored regularly. The frequency of occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 8 publications
2
26
0
1
Order By: Relevance
“…In our earlier study, p,p 0 DDE, p,p 0 DDT, and p,p 0 DDD residues have been reported in human breast milk samples from this region (Bedi et al 2013). In this study, the occurrence of endosulfan residues could be due to the presence of endosulfan residues in animal feed and fodder because contamination of animal feed has been reported earlier by many investigators (Deka et al 2004;Nag and Raikwar 2011).…”
Section: Contamination Patterns Of Pesticide Residues In Bovine Milksupporting
confidence: 62%
“…In our earlier study, p,p 0 DDE, p,p 0 DDT, and p,p 0 DDD residues have been reported in human breast milk samples from this region (Bedi et al 2013). In this study, the occurrence of endosulfan residues could be due to the presence of endosulfan residues in animal feed and fodder because contamination of animal feed has been reported earlier by many investigators (Deka et al 2004;Nag and Raikwar 2011).…”
Section: Contamination Patterns Of Pesticide Residues In Bovine Milksupporting
confidence: 62%
“…Cheema et al (2004) have also reported the presence of chlorpyrifos in 6.7% of milk samples collected from Punjab (India), and concentrations in all of these samples exceeded MRL values. In some previous reports from India, animal concentrate feed samples were found to be positive for endosulphan sulphate, chlorpyrifos, phorate, monocrotofos, dimethoate, diazinon, carbaryl p,p'-DDE and p,p'-DDT isomers residues Nag and Raikwar, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Agrochemicals that bioaccumulate should not be considered for registration in the first place, given the problems they cause, as the dark history of organochlorines and chlorfluazuron insecticides has demonstrated. Such chemicals are still present in agricultural soils [89] and are being transferred to animal tissues [90][91][92].…”
Section: Exposure Assessmentmentioning
confidence: 99%